2020
DOI: 10.11603/bmbr.2706-6290.2020.3.11357
|View full text |Cite
|
Sign up to set email alerts
|

Значення Маркерів Ендогенної Інтоксикації В Прогностичній Оцінці Ішемічно-Реперфузійного Синдрому Кінцівки

Abstract: Резюме. Застосування кровоспинного джуга є перевіреним засобом первинної медичної допомоги. Проте системні порушення, як і ультраструктурні в ділянці компресії, здатні суттєво погіршувати стан трав­мованого організму. Встановлення вираження ендогенної інтоксикації є важливим аспектом розуміння перебігу ішемічно-реперфузійного синдрому (ІРС) кінцівки. Мета дослідження – вивчити маркери ендогенної інтоксикації у сироватці крові в умовах впливу стресових чинників та їх поєднання. Матеріали і методи. Д… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In general, analyzing the dynamics of the activity catalase -the enzyme of the antioxidant system -we can identify the following pathogenetic factors that underlie similar changes. Previously we have found that each of these types of experimental interventions contributed to the growth of endogenous intoxication (EI) and stress impact for excretory renal function and the detoxifying role of the liver [16,17]. In this case, the more significant the level of EI, the more expressed suppression of antioxidant protection in almost all internal organs [18], and of course, in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In general, analyzing the dynamics of the activity catalase -the enzyme of the antioxidant system -we can identify the following pathogenetic factors that underlie similar changes. Previously we have found that each of these types of experimental interventions contributed to the growth of endogenous intoxication (EI) and stress impact for excretory renal function and the detoxifying role of the liver [16,17]. In this case, the more significant the level of EI, the more expressed suppression of antioxidant protection in almost all internal organs [18], and of course, in the liver.…”
Section: Discussionmentioning
confidence: 99%